Corporate – NGO Partnership for Successful CSR Programs – A Study with Reference to Selected Indian Automobile Companies - Sangita Maji (International Journal of Management Studies (IJMS), 2021)
This paper attempts to understand the work done by a private sector organization in the field of corporate social responsibility (CSR) in partnership with NGO and examine the role of NGOs in achieving the targeted CSR. We have selected three Indian auto mobile companies, TATA Motors Ltd., Hero Motocorp. Ltd. and Mahindra & Mahindra Ltd. for that purpose. This study is based on the secondary data and was collected through their web portal. The findings are that major CSR related activities though Implementing partner (NGO) revolve around similar areas for all three sectors, focusing on education and employability and Yet the policies and procedures regarding corporate social responsibility were structured in the companies act 2013 and it has been made compulsory. But TATA Motors irrespective their continuous losses carried on its CSR activities in partnership with NGO. The focus of organizations should not only be conduction of CSR, but creating a sustainable improvement of the society.